MULTIPLE INHERITANCE UNTUK C++ - Anwar, Khoerul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Multiple inheritance is the ability of the class to provide more of a super class. Multiple inheritance in a programming language to support a program to be structured as a collection of inheritance lattice of a collection of inheritance tree. Multiple inheritance recognized to be an important structuring tool. It is as well as the recognition that multiple inheritance is a fairly difficult / complex in a programming language, is difficult to implement, and costly to run. Here the authors will try to explain that none of the three estimates are true. Keywords: Multiple Inheritance, Super Class